Reamputation stumps below knee - Viktor I. Shevchuk; Yurii O. Bezsmertnyi; Yankai Jiang; Halyna V. Bezsmertna; Tetyana V. Dovgalyuk (Medicinski glasnik, 2021)
Aim: To investigate rehabilitation outcomes of patients with malformed tibial stumps. Methods: Observations included 421 patients with residual limb diseases and malformations (extensive inactive scars adhered to the bone, excessively long or short stumps, bone filing, osteomyelitis of the stump, muscle attachment to the skin scar, excessive mobility and deviations of the fibula, improper filing). Four hundred and thirty-six (436) reconstructive surgeries were performed. A follow-up period was from 6 months to 15 years. Radiological, ultrasonic, tensometrical, and histological methods were used. Results: Due to the frequent combination of several malformations and diseases in the same patient, non-free skin grafting with displaced dermal-subcutaneous flaps, which cover rather large defects, was widely used. The surgeries were performed simultaneously and allowed for reconstruction without shortening the bone lever stump. Complications in the form of marginal necrosis were obtained in three (0.71%) patients. The improved technique of muscle grafting with the fixation of muscles to the bone provided an elastic stump covering the bone filing. The authors have developed original methods of surgery to create a bone block of the tibia, which make it possible to obtain painless, highly functional stumps using partial support and ensure long-term use of modern prosthesis designs in 100% of cases. Conclusion: Non-free dermal plasty with cutaneous-subcutaneous flap is the method of choice for closing skin defects on the residual limb. Muscle-bone fixation permits to eliminate some residual limb defects and to form an elastic muscular residual limb with closed bone filaments. Synostosis formation in different ways considerably improves functional quality of the residual limb.
Keywords: bone synostosis; reconstructive surgery; stump